Nutritional Value Quality of Banana Stem Waste and Field Grass as Sheep Feed Through Silage Technology - Ardigurnita, Firgian; Rahayu, Novia; Nijam Al-Azmani, Muhammad; Mau’idoh Hasanah, Agnia (Bulletin of Applied Animal Research, 2026)
Research on the combination of field grass and banana stems through silage technology is one alternative for providing ruminant livestock feed. The objectives of this study were (1) to determine the quality of the nutritional value of silage feed combination of field grass and banana stems; (2) to determine the best balance of silage feed combination of field grass and banana stems. The method used was experimental using a Completely Randomized Design (CRD). The treatments tested consisted of 4 treatments and 5 replications. P0 (100% field grass); P1 (90% field grass + 10% banana stems); P2 (80% field grass + 20% banana stems); P3 (70% field grass + 30% banana stems). All treatments were made into silage with the addition of 8% pollard, 1% molasses and 1% rice washing water. The variables observed included dry matter value, ash content, crude fiber, crude protein, crude fat, ash, BETN and TDN. The results of the study showed that silage of field grass and banana stems can be used as alternative feed for local sheep. The combination of field grass and banana stems can increase the nutritional value of crude protein, TDN and BETN significantly different. The best feed silage balance was obtained in treatment (P3) with a combination of 70% field grass and 30% banana stems. Keywords: Banana Stem, Fermentation, Agricultural Waste, Field Grass, Silage.